Identification and Validation of Circular RNAs in Mouse Tissues and in a Transverse Aortic Constriction Induced Heart Hypertrophy Model - Schubert, Florian; Justus Liebig University Giessen (My University, 2023)
Circular RNAs represent a subclass of RNAs characterized by a loop structure and high stability in various environments. Recently, numerous circRNAs were demonstrated to play crucial roles in disease pathways, amongst others by sponging regulatory miRNAs and thereby regulating post-transcriptional gene control. Pathological cardiac hypertrophy is a process, in which the heart undergoes various adaptive processes leading to a reduced ejection fraction and subsequently to arrhythmias, heart failure and death. To date, the role of circRNAs in this pathology has been poorly characterized. In this study, we made use of an in-house circRNA detection pipeline to identify novel circRNA candidates in soleus muscle and heart. Candidates were validated and characterized by RT-PCR, as well as Sanger sequencing combined with RNAse R enrichment assays. Subsequently, expression profiles were investigated by quantitative and semi-quantitative RT-PCRs in various tissues. Ultimately, altered circRNA expression was studied in a TAC heart hypertrophy mouse model using a microarray-based transcriptome profiling. As a result, numerous de novo circRNA candidates were identified in soleus muscle, as well as in the heart. In total, 4 selected circRNA candidates from soleus muscle, including circZfp827, circNeb, circSec24b and circNfix, were experimentally verified, demonstrating the accuracy of the in-house circRNA detection pipeline. All investigated circRNAs are co-expressed with their linear counterparts and display tissue- and cell-type-specificity, indicating regulatory mechanisms in circRNA formation and potential biological functions. Quantification of circRNAs identified in heart revealed significant differential expression of selected circRNAs compared to their linear counterparts. Additionally, microarray analysis detected a significantly altered expression of nearly 400 circRNAs in a murine heart hypertrophy model. Interestingly, a subset of these circRNAs either derive from host genes, or are predicted to interact with miRNAs, involved in essential signaling pathways of hypertrophy pathogenesis. Until now, our approach provides one of the first microarray-based studies of differentially expressed circRNAs in a TAC-induced hypertrophy model. Previous reports, based on RNA sequencing data, did not provide conclusive data on altered circRNA expression. In the future, validation of differential expression of these circRNA candidates by qRT-PCR and Sanger sequencing of the back-splice junction in combination with functional assays may provide new insights into post-transcriptional regulatory networks involved in cardiac hypertrophy and may offer new biomarkers.
Keywords: circRNA; heart hypertrophy; murine; mouse; TAC; transverse aortic constriction; ddc:610